GENETIC MODEL OF MUD VOLCANISM OF THE KERCH PENINSULA (SCIENTIFIC AND APPLIED ASPECTS) - Nesterovskyi V.A. (Геологія і корисні копалини Світового океану, 2021)
The work is devoted to the results of many years of research and observations of mud volcanoes on the Kerch Peninsula. It aims to reveal the most important factors and aspects related to their origin, activity and impact on the geological history of the region. About 50 fossil and modern mud volcanoes have been defined on the Kerch Peninsula and the adjacent part of the water area. Their activity is consistent with the phases of activation of the alpine tectogenesis of the Crimean-Caucasian segment and is intermittent and impulsive. In the geological history of the peninsula, four main bursts of mud volcanic activity are clearly recorded: in the Upper Maikop, Chokrak-Karagan, Sarmatian and Cimmerian. Its greatest activity is manifested in the late Miocene and early Pliocene. Favorable factors for the development of mud volcanoes within the peninsula are the presence of a thick layer of plastic clays enriched in water and gas fluids, the widespread development of brachyanticlinal folds in the Neogene structural surface and a network of deep faults and fractures. The activity of mud volcanoes is associated with the formation of specific compensation structures – depressed synclines, which have become widespread on the Kerch Peninsula. The latter, depending on the paleogeographic conditions (sea, land) and the structural position of volcanoes in the anticlines, have acquired different specifics of structure and filling. Some depressed synclines are associated with iron ore deposits, which differ from typical iron ores of the mulde type by significant capacity, structural and textural features and material composition. Components of hydrothermal and exogenous origin have been defined in the products of mud volcanism: mud gases, mud waters, mud breccias, which indicates the genetic connection of this phenomenon with deep and near-surface processes. In addition, liquid, solid and gaseous hydrocarbons are often detected in volcanic eruptions. The latter are a criterion for searching for oil and gas at depth. Mud volcanoes of the Kerch Peninsula are a unique testing ground for monitoring the processes of modern mineral formation, the dynamics of deep processes and seismic activity in the region.